70.1.7 problem 2.2 (i)

Internal problem ID [14297]
Book : Nonlinear Ordinary Differential Equations by D.W.Jordna and P.Smith. 4th edition 1999. Oxford Univ. Press. NY
Section : Chapter 2. Plane autonomous systems and linearization. Problems page 79
Problem number : 2.2 (i)
Date solved : Tuesday, January 28, 2025 at 06:25:56 AM
CAS classification : system_of_ODEs

\begin{align*} \frac {d}{d t}x \left (t \right )&=3 x \left (t \right )-y \left (t \right )\\ \frac {d}{d t}y \left (t \right )&=x \left (t \right )+y \left (t \right ) \end{align*}

Solution by Maple

Time used: 0.028 (sec). Leaf size: 30

dsolve([diff(x(t),t)=3*x(t)-y(t),diff(y(t),t)=x(t)+y(t)],singsol=all)
 
\begin{align*} x \left (t \right ) &= {\mathrm e}^{2 t} \left (c_{2} t +c_{1} \right ) \\ y \left (t \right ) &= {\mathrm e}^{2 t} \left (c_{2} t +c_{1} -c_{2} \right ) \\ \end{align*}

Solution by Mathematica

Time used: 0.002 (sec). Leaf size: 44

DSolve[{D[x[t],t]==3*x[t]-y[t],D[y[t],t]==x[t]+y[t]},{x[t],y[t]},t,IncludeSingularSolutions -> True]
 
\begin{align*} x(t)\to e^{2 t} (c_1 (t+1)-c_2 t) \\ y(t)\to e^{2 t} ((c_1-c_2) t+c_2) \\ \end{align*}